Facilitators to the transition to post-school life of students with intellectual disability: A case study. - Alves, Sonia Vanessa (2019)
This case study aims at identifying facilitators to the transition to post-school adult living of an adolescent with Intellectual Disability (ID). ID involves impairments of general mental abilities that impact intellectual and adaptive functioning, thus restricting autonomy. We present recommendations for the intervention and a description of the school role in the transition planning to post-school adult living, as well as the legal framework for the applicable educational measures and resources. We also discuss the barriers to the employability of people with intellectual disabilities and the politics and supporting measures for access to employment. In the investigation, we applied a set of data collection tools – documentary research, a sociometric test, a self-concept scale and semi-structured interviews –, in order to characterize the functioning profile of an adolescent with mild to moderate ID and describe the parents’ and teachers’ perceptions and expectations about his transition to post-school adult living. We, then, suggest intervention guidelines which will optimise the facilitators to the transition to post-school adult living. Following an evaluation of the educational measures which have been applied through his school pathway, we have concluded that family expectations towards post-school adult living include material self-sufficiency, self-realization and job satisfaction, arising the latest from obtaining professional qualification; family’s and teachers’ expectations on employment inclusion focus on two personality and careers types – conventional and realistic. The problems and difficulties that may foreseeably limit future projects are: deficits on the autonomy and adaptive behaviour, problems of emotional and behavioural self-regulation, in personal relationships and in responsibility and social judgment, as well as difficulties in adjusting future career options and in obtaining professional qualification/certification. Finally, we present some recommendations, so that transition planning to post-school adult living may provide vocational orientation which will be adequate to the adolescent’s specific functioning and needs, and grant him access to a secondary education professional training course that will provide him with a professional qualification, with curricular adaptations, so that his learning achievements are relevant for the acquisition of competences that will constitute facilitators to the employment inclusion. The school should also relate the development of academic competences to job training and develop educational processes, which will promote autonomy and responsibility. It would also be advisable to provide parental psychoeducational activities, ensuring that the family support will be a facilitator rather than a barrier to the autonomy, self-determination and social inclusion.